Identifying sectoral impacts on global scarce water uses from multiple perspectives. (15th July 2021) - Yang, Xuechun; Liang, Sai; Qi, Jianchuan; Feng, Cuiyang; Qu, Shen; Xu, Ming
Abstract: Scarce water uses driven by hotspots in production and consumption stages of global supply chains have been well studied. However, hotspots in primary inputs and intermediate transmission stages also leading to large amounts of global scarce water uses are overlooked. This gap can lead to the underestimation of the impacts of certain nation sectors on global scarce water uses. This study identifies critical primary suppliers and transmission centers in global supply chains contributing to scarce water uses, based on environmentally extended multi‐regional input‐output (EE‐MRIO) model and complex network analysis methods. Results show that some critical primary suppliers (e.g., the service auxiliary to financial intermediation sector in the United States and the financial intermediation services sector in India) and transmission centers (e.g., the raw milk sector in the United States and the transmission services of electricity sector in China) are unidentifiable in previous studies. These findings provide hotspots for supply‐side measures (e.g., optimization of primary input and product allocation behaviors) and productivity improvement measures. The critical inter‐sectoral transactions (mainly involving the agricultural and food products sectors in India, China, and the United States) further provide explicit directions for these measures. Moreover, this study conducts a community detection, which identifies communities (i.e., the clusters of nation sectors closely interconnected) leading to global scarce water uses. Most of the communities involve sectors from different nations, providing foundations for international cooperation strategies.